Development and Assessment of a Miniaturized Test Rig for Evaluating Noise Reduction in Serrated Blades Under Turbulent Flow Conditions - Andrei-George Totu; Cristian-Teodor Olariu; Andrei-Tudor Trifu; Andreea-Cătălina Totu; Grigore Cican (Acoustics)
The implementation of serrated stator blades in axial compressor and fan stages offers significant advantages, such as enhanced performance and reduced noise levels, making it a practical and cost-effective solution. This study explores the impact of serrated blade design on noise reduction under specific engine operating conditions. A small-scale experimental test setup with a turbulence-inducing grid was designed for testing multiple grid sizes in order to identify the most promising configuration which replicates rotor–stator interaction. Numerical simulations and early experimental tests in an anechoic chamber using a four-blade cascade configuration at an airflow speed of 50 m/s revealed a small but notable noise reduction in the 1–6 kHz range for a partially matched grid–blade geometry. Serrated blades demonstrated an overall sound pressure level reduction of 1.5 dB and up to 12 dB in tonal noise, highlighting the potential of cascade configurations to improve acoustic performance in gas turbine applications.